Pravica do popravila kot sredstvo za doseganje trajnostnosti - Kalin, Tjaša (Pravni letopis, 2024)
The European Union is actively advocating for a greener economy. As part of the European Green Deal, a coordinated strategy for a climate-neutral, resource-efficient, and competitive economy has been adopted, which includes the expansion of the circular economy. Within the framework of the New circular economy action plan, the European Commission has worked to strengthen the role of consumers in the policy for sustainable products, primarily through the establishment of a new right to repair. Repairing is more efficient and sustainable than recycling, as it saves energy, materials, water, and also reduces transportation costs. The right to repair, as the name suggests, grants individuals the right to repair purchased goods either by themselves or through an independent repairer, or one of their choosing. The premise is that the individual has purchased the goods or device, thereby becoming the owner, and should consequently have the right to use, maintain, and repair the goods in the manner they deem most appropriate. In June 2024, a new Directive on common rules promoting the repair of goods (R2R directive) was adopted, fulfilling the European Commission’s priority regarding the green transition and the goal of sustainable consumption. The aim of the directive is to encourage repair and reuse when faulty goods can be repaired or refurbished. It provides consumers with tools to increase transparency and improve repair conditions, while imposing an obligation on manufacturers to repair certain goods even outside the legal guarantee.
Keywords: commercial guarantee; Direktiva R2R; legal guarantee for conformity of goods; obvezno jamstvo za skladnost blaga; pravica do popravila; R2R directive; right to repair; sustainable consumption; trajnostna potrošnja; tržna garancija